The PD-1 expression balance between effector and regulatory T cells predicts the clinical efficacy of PD-1 blockade therapies - Kumagai, Shogo; Togashi, Yosuke; Kamada, Takahiro; Sugiyama, Eri; Nishinakamura, Hitomi; Takeuchi, Yoshiko; Vitaly, Kochin; Itahashi, Kota; Maeda, Yuka; Matsui, Shigeyuki; Shibahara, Takuma; Yamashita, Yasuho; et al. (Nature immunology, 2020)
Immune checkpoint blockade has provided a paradigm shift in cancer therapy, but the success of this approach is very variable; therefore, biomarkers predictive of clinical efficacy are urgently required. Here, we show that the frequency of PD-1 + CD8 + T cells relative to that of PD-1 + regulatory T (T reg ) cells in the tumor microenvironment can predict the clinical efficacy of programmed cell death protein 1 (PD-1) blockade therapies and is superior to other predictors, including PD ligand 1 (PD-L1) expression or tumor mutational burden. PD-1 expression by CD8 + T cells and T reg cells negatively impacts effector and immunosuppressive functions, respectively. PD-1 blockade induces both recovery of dysfunctional PD-1 + CD8 + T cells and enhanced PD-1 + T reg cell–mediated immunosuppression. A profound reactivation of effector PD-1 + CD8 + T cells rather than PD-1 + T reg cells by PD-1 blockade is necessary for tumor regression. These findings provide a promising predictive biomarker for PD-1 blockade therapies. Checkpoint blockade is effective in only a subset of patients; therefore, biomarkers that can predict efficacy would be clinically highly valuable. Nishkawa and colleagues develop a biomarker based on PD-1 positivity of effector and regulatory T cells in the tumor microenvironment that accurately predicts the effectiveness of checkpoint blockade in patients.